Intensitas, Kualitas, Derajat Relevansi Supervisi Akademik Dalam Meningkatkan Kinerja Guru Madrasah Di Era Teknologi Komunikasi - Mustaqim Mustaqim; Muhammad Hanif Fahmi; Lian Agustina Setiyaningsih (Tadbir : Jurnal Studi Manajemen Pendidikan, 2020)
The failure of academic supervision in various areas is more dominant due to inappropriate scheduling. In addition, the awareness of the importance of implementing academic supervision is also an inhibiting factor in the implementation of supervision. The era of media technology is a challenge for educational institutions from elementary to high levels. The problems that arise are related to the habit of teaching and learning processes based on communication technology. An interesting phenomenon is that Central Java ranks third in having the most madrasas in Indonesia. So it is necessary to know the mechanism for the implementation and evaluation of academic supervision. The challenge of providing supervision in the era of communication technology is seen from three points of view, namely intensity, quality, degree of relevance associated with teacher performance in madrasah. The research method used is mixed research by relying on the strength of the description that comes from the informant. And also involve respondents to explore quantitative data. The informants involved were 5 school principals and supervisors. Meanwhile, there are 190 madrasah teachers in Central Java. Data obtained from interviews, questionnaires and documentation. Data analysis used the Milles and Huberman pattern. The results of this study explain that the intensity, quality and degree of relevance of educational supervision are in the average category. This condition is able to improve the performance of madrasah teachers in Central Java. The teachers support online supervision and the method preferences tend to be CCTV, virtual and fingerprint.